Ocean impact on Southern African climate variability and water resources - (:unkn) unknown (My University, 2019)
The oceans have a profound influence on the weather and climate of South Africa. Not only, most rainfall comes from condensation of water vapor originating from the flux of moisture from ocean to atmosphere but the temperature of the remote and surrounding oceans have an impact of the interannual variability of rainfall. A good example of this remote effect is the impact of the ocean during El Nino when the temperature of the Pacific and Indian Ocean is higher than normal. This creates more rainfall above the higher sea surface temperature thus modifying the global Walker and Hadley circulation. Air usually rises in the equatorial regions, especially above the ocean creating rainfall which increases further the ascending motion of air. The air is eventually pushed poleward and then cools and sinks in the subtropical region where Southern Africa sits, creating high pressure and subsidence which is not favorable to rainfall. This is one of the teleconnection mechanisms linking remote oceanic region to South Africa. The aim of the project was to better understand the role of the ocean on weather, climate and rivers of Southern Africa. Little work has been done to connect streamflow to the El Nino Southern Oscillation previous to that project. We also looked at the tropical Atlantic Ocean, which is closer to us although but smaller where a similar phenomenon to El Nino occurs, the Benguela Nino. Closer to South Africa, the Agulhas Current was known to impact the atmosphere above it due to high turbulent flux of moisture from sea to atmosphere. In the past, due to low resolution reanalyzed climate data that did not integrate the Agulhas Current, it was not possible to study the impact of the Agulhas Current on local climate with reanalyzed climate dataset such as ERA or NCEP. This project made some important advance to that matter using new high resolution reanalyzed climate data and a model and
Keywords: African Research